2012
DOI: 10.1038/nature11307
|View full text |Cite
|
Sign up to set email alerts
|

TNF receptor 1 genetic risk mirrors outcome of anti-TNF therapy in multiple sclerosis

Abstract: Although there has been much success in identifying genetic variants associated with common diseases using genome-wide association studies (GWAS)1, it has been difficult to demonstrate which variants are causal and what role they play in disease. Moreover, the modest contribution these variants make to disease risk has raised questions regarding their medical relevance2. We have investigated a single nucleotide polymorphism (SNP) in the TNFRSF1A gene, that encodes TNF receptor 1 (TNFR1), which was discovered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
236
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(250 citation statements)
references
References 31 publications
12
236
0
2
Order By: Relevance
“…A polymorphism of multiple sclerosis in the TNFRSF1A gene, encoding for TNFR1, has been shown to mimic TNF blockade and cause a more severe clinical outcome (61). Future studies are needed to investigate the reasons for differential responses to anti-TNF therapy among EAE, MS, and other neuroinflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A polymorphism of multiple sclerosis in the TNFRSF1A gene, encoding for TNFR1, has been shown to mimic TNF blockade and cause a more severe clinical outcome (61). Future studies are needed to investigate the reasons for differential responses to anti-TNF therapy among EAE, MS, and other neuroinflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…24 Transethnic studies have demonstrated substantial genetic overlap between ethnically remote populations; 106 109 The SNP leads to loss of the transmembrane domain of the receptor, and the risk SNP for MS (protective for AS) leads to increased serum soluble TNF receptor. 110 TNF inhibition, including by decoy TNF receptor therapies, is highly effective for AS and many other immune-mediated diseases, but its use can be complicated by de novo development of MS, and in MS itself, it can exacerbate disease. Although this is a retrospective example, it demonstrates the potential of using genetics to predict toxicities.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…A GWAS screening revealed a SNP (rs 1800693), in the tumor necrosis factor receptor (TNFR) gene, that was associated with disease susceptibility. This genetic variation was responsible for a rare soluble form of TNFR that blocks circulating TNF 4 and has been suggested that TNF blockage could trigger MS. Curiously, anti-TNF drugs (such as infliximab) largely used for other inflammatory diseases such as rheumatoid arthritis, psoriasis and Crohn´s disease can also trigger multiple sclerosis indicating clearly that genome-based analysis unveiling SNPs are being associated with different complex diseases and their mechanisms of action can be copied using different types of immunobiologicals or drugs.…”
Section: Perspectivas Perspectivesmentioning
confidence: 99%